2018
DOI: 10.1083/jcb.201707004
|View full text |Cite
|
Sign up to set email alerts
|

Cell-free formation and interactome analysis of caveolae

Abstract: Caveolae are linked to signaling protein regulation through interactions with caveolins. We describe a cell-free system for the biogenesis of caveolae and show phosphorylated-caveolins preferentially bind signaling proteins. Our validation in vivo shows that phosphorylated CAV1 recruits TRAF2 to the endosome to form a signaling platform.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
58
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 52 publications
(62 citation statements)
references
References 95 publications
4
58
0
Order By: Relevance
“…A, Cav-a-tGFP localizes at the peri-nucleus in Ciona embryos at 14 hpf. 17,18 In the urochordate animal Ciona, our results using a cell-free system, as well as in vivo experimental results, revealed that Cav-a was recruited to the plasma membrane, and generated membrane invaginations that were morphologically similar to vertebrate caveolae, but with a wider "neck". C, At 21 hpf, Cav-a-tGFP specially enriches at the apical domains.…”
Section: Ascidian Cav-a Forms Membrane Curvature In Both In Vitro Amentioning
confidence: 70%
See 4 more Smart Citations
“…A, Cav-a-tGFP localizes at the peri-nucleus in Ciona embryos at 14 hpf. 17,18 In the urochordate animal Ciona, our results using a cell-free system, as well as in vivo experimental results, revealed that Cav-a was recruited to the plasma membrane, and generated membrane invaginations that were morphologically similar to vertebrate caveolae, but with a wider "neck". C, At 21 hpf, Cav-a-tGFP specially enriches at the apical domains.…”
Section: Ascidian Cav-a Forms Membrane Curvature In Both In Vitro Amentioning
confidence: 70%
“…18 The results showed that Ciona Cav-a but not Cav-b induced membrane curvature similar to that induced by human Cav1 (red circle in Figure 3A). 18 The results showed that Ciona Cav-a but not Cav-b induced membrane curvature similar to that induced by human Cav1 (red circle in Figure 3A).…”
Section: Cav-a Forms Caveola-like Structures By Inducing Membrane Cmentioning
confidence: 78%
See 3 more Smart Citations